Microtriplication of 11q24.1: a highly recognisable phenotype with short stature, distinctive facial features, keratoconus, overweight, and intellectual disability. Issue 9 (26th May 2011) - Beneteau, Claire; Landais, Emilie; Doco-Fenzy, Martine; Gavazzi, Cyrille; Philippe, Christophe; Béri-Dexheimer, Mylène; Bonnet, Céline; Vigneron, Jacqueline; Walrafen, Pierre; Motte, Jacques; Leheup, Bruno; Jonveaux, Philippe
Abstract : Background: Partial tetrasomy is mainly described as a cytogenetically visible rearrangement due to a supernumerary chromosome (i(12p), i(18p), inv dup(15)). Except for chromosome 15q11q13, intrachromosomal triplications are rare and so far not associated with a recognisable phenotype. Methods and results: This report describes two unrelated patients with a de novo non-recurrent submicroscopic interstitial triplication 11q24.1 detected with array comparative genomic hybridisation and confirmed by fluorescence in situ hybridisation, molecular combing, and quantitative PCR. Microsatellite analysis suggested that a common mechanism of rearrangement might have been involved. These patients share remarkably similar clinical features including distinctive facial dysmorphisms, short stature with small extremities, keratoconus, overweight, and intellectual disability. The overlapping region of 1.8 Mb contains 11 RefSeq genes and three microRNA related genes. Interestingly, the overexpression of ASAM, a gene encoding an adipocyte specific adhesion molecule, may contribute to patients' obesity. Upregulation of BILD, known to mediate apoptosis in a caspase dependent manner, could deserve further investigation into the pathological mechanism of keratoconus. Conclusion: Isolated duplications of distal 11q region have been previously reported and associated with intellectual disability but without a consistent set of clinical features. These findings support the proposal that microtriplication 11q24.1 is a well recognisable clinical entity.